Vermicomposting: A technology for vermiremediation of heavy metals from sewage sludge and animal dung - Deepka Kumar Bhartiya; Gorakh Nath; Keshav Singh (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The present study to investigate the earthworm Eisenia fetida was a chief organism for accumulation of heavy metals (Pb, Cr, and Cd) in their body tissue from sewage sludge with different combinations of animal dung and converted into rich organic vermicompost which plays a beneficial role for environment, animals and human health.